Mechanisms underlying the predictive power of high skeletal muscle uptake of FDG in amyotrophic lateral sclerosis - Marini, Cecilia (EJNMMI Res, 2020)
BACKGROUND: We recently reported that enhanced [18F]-fluorodeoxyglucose (FDG) uptake in skeletal muscles predicts disease aggressiveness in patients with amyotrophic lateral sclerosis (ALS). The present experimental study aimed to assess whether this predictive potential reflects the link between FDG uptake and redox stress that has been previously reported in different tissues and disease models. METHODS: The study included 15 SOD1(G93A) mice (as experimental ALS model) and 15 wildtype mice (around 120 days old). Mice were submitted to micro-PET imaging. Enzymatic pathways and response to oxidative stress were evaluated in harvested quadriceps and hearts by biochemical, immunohistochemical, and immunofluorescence analysis. Colocalization between the endoplasmic reticulum (ER) and the fluorescent FDG analog 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxyglucose (2-NBDG) was performed in fresh skeletal muscle sections. Finally, mitochondrial ultrastructure and bioenergetics were evaluated in harvested quadriceps and hearts. RESULTS: FDG retention was significantly higher in hindlimb skeletal muscles of symptomatic SOD1(G93A) mice with respect to control ones. This difference was not explained by any acceleration in glucose degradation through glycolysis or cytosolic pentose phosphate pathway (PPP). Similarly, it was independent of inflammatory infiltration. Rather, the high FDG retention in SOD1(G93A) skeletal muscle was associated with an accelerated generation of reactive oxygen species. This redox stress selectively involved the ER and the local PPP triggered by hexose-6P-dehydrogenase. ER involvement was confirmed by the colocalization of the 2-NBDG with a vital ER tracker. The oxidative damage in transgenic skeletal muscle was associated with a severe impairment in the crosstalk between ER and mitochondria combined with alterations in mitochondrial ultrastructure and fusion/fission balance. The expected respiratory damage was confirmed by a deceleration in ATP synthesis and oxygen consumption rate. These same abnormalities were represented to a markedly lower degree in the myocardium, as a sample of non-voluntary striated muscle. CONCLUSION: Skeletal muscle of SOD1(G93A) mice reproduces the increased FDG uptake observed in ALS patients. This finding reflects the selective activation of the ER-PPP in response to significant redox stress associated with alterations of mitochondrial ultrastructure, networking, and connection with the ER itself. This scenario is less severe in cardiomyocytes suggesting a relevant role for either communication with synaptic plaque or contraction dynamics.